Childhood Trauma and Non-suicidal Self-Injury Among Chinese Adolescents: The Mediating Role of Psychological Sub-health - Huang, Cui; Yuan, Qiuyu; Ge, Menglin; Sheng, Xuanlian; Yang, Meng; Shi, Shengya; Cao, Panpan; Ye, Mengting; Peng, Ran; Zhou, Ruochen; Zhang, Kai; Zhou, Xiaoqin (Frontiers in Psychiatry, 2022)
The factors associated with non-suicidal self-injury (NSSI) of adolescents have been widely researched. However, the underlying mechanism of the relationship between childhood trauma and NSSI is limited. This study aimed to explore the risk factors for NSSI among Chinese adolescents. Our hypothesis was that psychological sub-health (PSH) played a mediating role between childhood trauma and NSSI. The Childhood Trauma Questionnaire, the Multidimensional Sub-health Questionnaire of Adolescent, and the self-report NSSI were used to measure childhood trauma, PSH, and NSSI. Structural equation model (SEM) was performed to verify our hypothesis. The results showed that 33.9% of the participants in our survey had engaged in NSSI in the past year. Adolescents who were left-behind children or in primary schools were more likely to engage in NSSI. Additionally, 56.2% of the participants had moderate to severe childhood trauma, and 26.1% of the participants had PSH. Furthermore, childhood trauma and PSH would increase the risk of NSSI by 2 times(B=0.79, p＜0.01) and 5 times(B=1.64, p＜0.01), respectively. SEM was established(p=0.512) and the goodness-of-fit indices were examined(CMIN/DF=0.892; GFI=0.997; AGFI=0.992; NFI=0.991; RFI=0.980; IFI=1.00; TLI=1.00; CFI=1.00; RMSEA＜0.001). The SEM indicated that childhood trauma positively predicted NSSI both directly and indirectly through PSH. PSH has been confirmed to have partial mediating effects between childhood trauma and NSSI. The assessment of PSH may be an operable and effective method to screen and predict NSSI. Meanwhile, the intervention of childhood trauma and PSH may effectively prevent and reduce the occurrence of NSSI among adolescents.